2022
DOI: 10.1002/app.52764
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and dissociation behavior of polypropylene‐graft‐maleic anhydride

Abstract: Understanding the dissociation behavior of functional polymers can help tailor materials for performance in target applications. Polypropylene-graft-maleic anhydride (PP-g-MA) undergoes partial hydrolysis to form polypropylenegraft-succinic acid (PP-g-SA) due to trace atmospheric moisture during extrusion. While there have been reports on the relationship between interfacial and antioxidant properties for functional polymers, PP-g-SA's behavior has yet to be explored despite its widespread occurrence. Here, PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…20 Previous research has demonstrated the significance of pH conditions on radical scavenging kinetics. 66,67 Therefore, it is worth noting that the ABTS assay performed in this work was executed at pH 7.4, which is below the pK a value of curcumin's enolic hydrogen (7.8). 68 Consequently, curcumin was not deprotonated under these assay conditions, suggesting that ABTS radical scavenging by PLA-g-Cur films was limited to the HAT mechanism.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…20 Previous research has demonstrated the significance of pH conditions on radical scavenging kinetics. 66,67 Therefore, it is worth noting that the ABTS assay performed in this work was executed at pH 7.4, which is below the pK a value of curcumin's enolic hydrogen (7.8). 68 Consequently, curcumin was not deprotonated under these assay conditions, suggesting that ABTS radical scavenging by PLA-g-Cur films was limited to the HAT mechanism.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…To facilitate homogenization of polymer pellets and reagent powders, isotactic PP and PP-g-MA were blended as described previously. 38 Briefly, PP was mechanically mixed with 50% w/w PP-g-MA and fed into a Process MA) through an attached volumetric feeder (11 mm volumetric single screw feeder for process 11 [MK2] by Thermo Electron, Germany) at 7% the maximum rate. Isotactic PP without blending was also prepared as a control for all analyses.…”
Section: Synthesis and Characterization Of Antioxidant Polypropylene ...mentioning
confidence: 99%
“…To facilitate homogenization of polymer pellets and reagent powders, isotactic PP and PP-g-MA were blended as described previously. 38 Briefly, PP was mechanically mixed with 50% w/w PP-g-MA and fed into a Process °C at the die. The extruded polymer filament was fed into a Vericut Pelletizer (ThermoFisher Scientific, Waltham, ME) using the L1 setting to form 0.5 mm granules of blended PP and PP-g-MA.…”
Section: Synthesis and Characterization Of Antioxidant Polypropylene ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The poplar cell wall was in situ polymerized with HEMA and 3-(methacryloxy) propyltrimethoxysilane (MAPTES) to improve its dimensional stability [ 21 ]. A functional monomer of unsaturated double bonds and polar carboxylic groups, maleic anhydride (MAh) is commonly used in grafting and copolymerization [ 22 , 23 ]. Lignocellulosic materials can attain higher hydrophobicity and dimensional stability by removing hydroxyl groups from wood polymers with organic anhydride.…”
Section: Introductionmentioning
confidence: 99%